The Role Of Information Technology In The Animation Industry - Yasa, Gede Pasek Putra Adnyana; Pratistha, Indra (Jurnal Scientia, 2024)
This research examines the role of information technology in the animation production process, focusing on how recent technologies have improved the efficiency and quality of production output. The main objective of this research is to explore the impact of various information technology-based tools and software on the creativity and productivity of animation teams. The research method used is a qualitative method with a case study approach in several animation studios in Bali. The theories underlying this research are visual communication theory and diffusion of innovation theory, which are used to understand how new technologies are adopted and applied in the animation industry. The results show that the integration of information technology in animation production not only accelerates the production process but also opens up opportunities for greater creative innovation. Technologies such as 3D animation software, cloud-based project management systems, and online collaboration tools have been shown to contribute significantly to the improvement of animation quality and teamwork effectiveness. These findings confirm the importance of investing in information technology for the animation industry to remain competitive in the global market.